Temperament and Character Dimensions in Narcotics Addicts and Normal people - Abbas Abolghasemi; Azar Kiamarsi; Sobel Momeni (Drug Control Headquarters, Research and Education Office, 2013)
Objective: The purpose of this study was to compare the temperament and character dimensions in narcotics addicted and normal persons. Method: The method of research was causative-comparative. The study sample consisted of 120 addicts and non addicts who had referred to 3 narcotics addicts treatment centers in Ardabil city. The subjects were selected through simple random sampling. To collect data, temperament/character inventory were used. Findings: The results showed that novelty seeking and harm avoidance in addicts is significantly greater than normal persons. Also, results showed that reward dependence, self-directedness, and cooperativeness in narcotics addicts is significantly lower than normal persons. Conclusion: The results show that temperament and character dimensions determine the addiction intensity in addicted people.